Prevention Program for People Living with Stroke in Low and Middle-Income Country: A Systematic Review - Aisyah Lahdji; Dwi Pudjonarko; Zahroh Shaluhiyah (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Non-communicable diseases (NCDs) are the primary factors responsible for mortality and impairment on a global scale. By 2030, it is estimated that non-communicable diseases will comprise 80% of the global population. According to the World Health Organization (WHO), the risk of stroke will grow by 50% for the entire global population by 2022. Currently, it is projected that 1 in 4 individuals will suffer from a strokeMethod: This review was reported using the “Preferred Reporting Items for Systematic Reviews and Meta-Analysis” guideline and written using the “Synthesis without Meta-Analysis” method. The included studies for this review followed several criteria, including randomized controlled trials (RCT), English and Bahasa articles, using population was people living with stroke, intervention was any prevention and disability limitation, and outcomes were prevention measurements (primary, secondary, and tertiary prevention).Results: The study yielded multiple efficacious and streamlined preventive interventions implemented for stroke patients. Emphasizing risk factors as the main strategy for preventing health issues, using pharmacological treatments such as polypill, aspirin, and vitamins as a supplementary measure under the guidance of medical physicians and cardiologists. In addition, tertiary preventive initiatives encompass more than just administering drug treatment; they also require adherence to pharmaceutical protocols